2018
DOI: 10.1002/ijc.31309
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic dysregulation of key developmental genes in radiation‐induced rat mammary carcinomas

Abstract: With the increase in the number of long-term cancer survivors worldwide, there is a growing concern about the risk of secondary cancers induced by radiotherapy. Epigenetic modifications of genes associated with carcinogenesis are attractive targets for the prevention of cancer owing to their reversible nature. To identify genes with possible changes in functionally relevant DNA methylation patterns in mammary carcinomas induced by radiation exposure, we performed microarray-based global DNA methylation and exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 60 publications
(111 reference statements)
1
18
0
Order By: Relevance
“…The red circle indicated the up-regulated circRNAs and the green ones indicated the down-regulated ones which mediated gene transcription [30]. Furthermore, aberrant methylation could lead to dysregulation of related transcription-factor genes, which might be closely bound up to irradiation [31,32]. KEGG analysis indicated that the lysine degradation was important, which was consistent with the results of GO analysis.…”
Section: Discussionsupporting
confidence: 75%
“…The red circle indicated the up-regulated circRNAs and the green ones indicated the down-regulated ones which mediated gene transcription [30]. Furthermore, aberrant methylation could lead to dysregulation of related transcription-factor genes, which might be closely bound up to irradiation [31,32]. KEGG analysis indicated that the lysine degradation was important, which was consistent with the results of GO analysis.…”
Section: Discussionsupporting
confidence: 75%
“…Moreover, various animal experiments have revealed that neutrons have a strong effect on mammary carcinogenesis (8). Other studies have revealed various genomic and epigenomic alterations in radiation-induced cancers (9,10). Although copy number aberrations are common in many types of tumors, there are only a few findings on genetic alterations of cancers induced by neutrons (11).…”
Section: Abstract Background/aim: Neutrons Are Used As a Type Of Higmentioning
confidence: 99%
“…As reported, VDR and p53 in irradiated HEK 293T was related to various biological effects, which mediated gene transcription [30] . Furthermore, aberrant methylation could lead to dysregulation of related transcription-factor genes, which might be closely bound up to irradiation [31,32] . KEGG analysis indicated that the lysine degradation was important, which was consistent with the results of GO analysis.…”
Section: Discussionmentioning
confidence: 99%